Dietary fiber as fat substitute in emulsified and cooked meat model system - Schmiele, Marcio; Chiarinelli Nucci Mascarenhas, Maria Cristina; Silva Barretto, Andrea Carla da [UNESP]; Rodrigues Pollonio, Manse Aparecida (Elsevier B.V., 2015)
Fat intake has been associated with increased risk of cardiovascular disease, obesity, and diabetes. The aim of this study was to reformulate meat products using amorphous cellulose fiber (Z-trim(R)) as a fat substitute. Based on a Response Surface Methodology, an emulsified and cooked meat model system was carried out with a standard formulation with 20 g/100 g pork fat, and replacement levels of pork fat (from 0 to 20 g/100 g) by amorphous cellulose fiber (from 0 to 1.5 g/100 g). The independent variables within the levels studied influenced the dependent variables emulsion stability (from 73.64 to 91.76 g/100 g), firmness (from 27.32 to 48.02 N), hardness (from 50.86 to 83.00 N), b* color coordinate (14 days) (from 13.08 to 14.45), and weight loss during storage (from 1.88 to 5.16 g/100 g). Comparing the fitted models to the results of the standard sample, it is possible to obtain products with 1.3 g/100 g amorphous cellulose fiber and 10 g/100 g pork fat (50% fat reduction), with technological characteristics similar to the standard sample. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fat substitute; Amorphous cellulose fiber; Meat emulsion; Emulsion stability; Texture